Body image satisfaction in badminton athletes (Research, Society and Development, 2022)
Body image is a multidimensional constructor that involves evaluation, perception and behaviors related to the appearance and function of the body being evaluated positively or negatively. The aim of this study was to verify body image satisfaction in badminton athletes from the city of Teresina (PI). This is a descriptive study with a quantitative approach, conducted with 16 badminton athletes, male and female from the city of Teresina-PI, aged between 18 and 40 years, chosen for convenience. The instruments used in the research were the Female Silhouette Scale (ESF), proposed by Kanno (2009) and the Male Silhouette Scale (ESM), proposed by Sousa (2011). Through statistical analysis, athletes in general are predominantly classified at a light and median level both with (43.75%) and high (12.5%), when stratification by gender, males are moderately more dissatisfied (57.14%) in relation to females (33.33%), but women demonstrated they are higher dissatisfied (22.22%). With regard to the Real Image in males (43.5%) they see themselves in the silhouette (05) with characteristics of eutrophy, while women (22.0%) see themselves among the silhouettes (03), (05) and (08) respectively with characteristics of hypertrophy and eutrophy, in the Ideal Image both male and female idealized silhouettes (03) with hypertrophy characteristics, respectively (57.0 %) and (33.0%). It is important that studies related to this theme be more explored, since there is a limitation of studies relating body image in performance athletes mainly in males.